If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2 + 8 + x + (-12) = (-17) + 9 -2 + 8 + x + -12 = (-17) + 9 Reorder the terms: -2 + 8 + -12 + x = (-17) + 9 Combine like terms: -2 + 8 = 6 6 + -12 + x = (-17) + 9 Combine like terms: 6 + -12 = -6 -6 + x = (-17) + 9 -6 + x = -17 + 9 Combine like terms: -17 + 9 = -8 -6 + x = -8 Solving -6 + x = -8 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + x = -8 + 6 Combine like terms: -6 + 6 = 0 0 + x = -8 + 6 x = -8 + 6 Combine like terms: -8 + 6 = -2 x = -2 Simplifying x = -2
| 6x+11x-25+13x-35+6x+35+8x+15+9x-5+7x+15=900 | | 10x-4+4+4+x-22=0 | | 8-(-3-7x)-2(5x+3)=36 | | n^2+2n-19=5 | | fx+1=9x+4 | | 10(10+8k)= | | 0.6768%= | | f(x+1)=9x+4 | | x^2+-2x+-4=0 | | -6(2n-7)+2(n+4)=-36 | | x-2x-4=0 | | 20(x-0.5)=70 | | 26-18=2(x-2) | | 540-8P=120+6P | | 4(8a+-8)= | | 8z=12 | | 2x-sin(0.5x)=0 | | 7x-12=15-4x | | 8x-(x-4)=7x | | =6P+540 | | y^2-2y-35= | | 4t-2= | | x+18+4x=-10-4x-17 | | t^2-8t=19 | | 58=-8(8m+5)-3-m+8 | | -7x+3y=38 | | 2x-(x+2)=-4 | | 19-x=14 | | 2(4-7)= | | 9t-6t+t-2= | | -109+x=34+12x | | -6-13=5x+18-4x |